THERMAL STRESS ALLEVIATION BY BIOSTIMULANT APPLICATION ON CANTALOUPE MELON SEEDS - Vendruscolo, E. P.; Martins, A. P. B.; Campos, L. F. C.; Seleguini, A.; dos Santos, M. M. (Revista Brasileira de Engenharia de Biossistemas, 2016)
It wasaimed with this study obtain information on the use of biostimulant on the mitigation of heat stress in the germination phase and early development of muskmelon. The study was conducted in a randomized block design in a 4x2 factorial scheme composed by doses of biostimulant (0, 4, 8, and 12 mL L-1) and temperatures (25°C and 40°C). Were evaluated the germination rate, the average time of germination, germination speed index, the initial seedling growth and dry mass of shoot and root seedlings. It was observed that the germination rate was enhanced by increasing doses biostimulant at both temperatures. However, the temperature of 40°C impairs the average time and germination rate index. There was a positive effect for the biostimulant only for seeds subjected to 40°C on the average time of germination and germination speed index, while at 25°C the biostimulant hurt the average germination time. Therefore, the biostimulant can be used to improve the initial development of melons in regions withhigh temperatures.